2021
DOI: 10.1371/journal.pcbi.1008155
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally specific temporal analyses of spike-train responses to complex sounds: A unifying framework

Abstract: Significant scientific and translational questions remain in auditory neuroscience surrounding the neural correlates of perception. Relating perceptual and neural data collected from humans can be useful; however, human-based neural data are typically limited to evoked far-field responses, which lack anatomical and physiological specificity. Laboratory-controlled preclinical animal models offer the advantage of comparing single-unit and evoked responses from the same animals. This ability provides opportunitie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 84 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Here, we took advantage of the MAP_BS’s output to present stimuli of opposing polarity and compare coincident events in the resulting stochastic spike trains. Consequently, by extracting and quantifying these envelope-sensitive components with sumcor analysis ( Fig 2C and 2E ), we could identify how envelope encoding was affected by the suppression of cochlear gain for differently degraded words [ 73 76 ] and provide a coherent rationale for our experimental observations ( Fig 2E and 2F ). The ASR, on the other hand, has been previously used as a proxy for human hearing, predicting the intelligibility of test digit sequences from their AN spike probabilities using a hidden Markov model [ 58 60 , 62 , 139 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Here, we took advantage of the MAP_BS’s output to present stimuli of opposing polarity and compare coincident events in the resulting stochastic spike trains. Consequently, by extracting and quantifying these envelope-sensitive components with sumcor analysis ( Fig 2C and 2E ), we could identify how envelope encoding was affected by the suppression of cochlear gain for differently degraded words [ 73 76 ] and provide a coherent rationale for our experimental observations ( Fig 2E and 2F ). The ASR, on the other hand, has been previously used as a proxy for human hearing, predicting the intelligibility of test digit sequences from their AN spike probabilities using a hidden Markov model [ 58 60 , 62 , 139 ].…”
Section: Discussionmentioning
confidence: 98%
“…Sumcor Test Nat is the average of the SCC (Average of normalised all-order histograms for Nat+ versus Test+ and Nat- versus Test-) and the cross-polarity correlogram (Average of normalised all-order histograms for Nat- versus Test+ and Nat+ versus Test-) between natural and Voc8/BN5/SSN3 conditions. All high-frequency oscillations (> characteristic frequency of AN fibre), associated with fine-structure leakage, were removed from sumcor s [ 73 , 76 ]. ρENV values ranged from 0 to 1 where 0 represents completely dissimilar spike trains and 1 represents identical spike patterns [ 50 , 73 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large CI value indicates highly reproducible spiking responses over repeated trials (Joris et al, 2006 ). In contrast to VS, which is narrowband (i.e., only the spectral component at frequency f is considered), CI is generally broadband, as it is a collective measure of multiple frequency components (Parida et al, 2021 ). SACs and CIs can be applied to both periodic and aperiodic signals and were used for characterizing the temporal coding properties of auditory nerve (AN) fibers (Dreyer and Delgutte, 2006 ; Heinz and Swaminathan, 2009 ; Huet et al, 2018 ; Heeringa et al, 2019 ), various neurons in the cochlear nuclei recorded in vivo (Gai and Carney, 2008 ; Steinberg and Peña, 2011 ; Recio-Spinoso, 2012 ; Keine et al, 2016 ) and in vitro (Street and Manis, 2007 ; Kreeger et al, 2012 ), and neurons in the auditory midbrain (Shackleton et al, 2009 ; Zheng and Escabí, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses of physiological data suggested that they should covary according to some monotonic, non-linear relationship (Dreyer and Delgutte, 2006 ; Joris et al, 2006 ). Parida and colleagues mathematically related peristimulus time histograms (PSTHs) to VS and CI under very general conditions (Parida et al, 2021 ). In the present study, we derive a mathematically rigorous relationship between VS and CI under certain assumptions for phase-locking.…”
Section: Introductionmentioning
confidence: 99%